47 Rehabilitation enablement in chronic heart failure (reach-HF) a multicentre randomised controlled trial of facilitated self-care rehabilitation intervention in heart failure with reduced ejection fraction. (June 2018) - Dalal, Hasnain; Jolly, Kate; Davis, Russell; Doherty, Patrick; Austin, Jackie; Lingen, Robin van; Warren, Fiona; Green, Colin; Wingham, Jenny; Britten, Nicky; Greaves, Colin; Abraham, Charles; et al.
Abstract : Introduction: Evidence from systematic reviews and meta-analyses of randomised trials has led the National Institute of health and Care Excellence (NICE) and international guideline bodies to recommend centre-based cardiac rehabilitation (CR) as an effective and safe intervention for heart failure. CR reduces the risk of hospitalisations and improves health related quality of life (HRQoL). Nevertheless, CR uptake for heart failure (HF) remains suboptimal and alternative delivery models, such as home-based programmes are therefore needed. The REACH-HF multi-centre trial (ISRCTN86234930 ) was designed to evaluate the effectiveness of a novel evidence-informed home-based rehabilitation intervention in heart failure with reduced ejection fraction (HFrEF) patients. Methods: Patients from 4 UK centres with a left ventricular ejection fraction of <45% were randomised 1:1 between January 2015 and February 2016 to the REACH-HF intervention (self-help manual facilitated by trained nurses or physiotherapists over 12 weeks) plus usual care (intervention group) or usual care alone (control group). Outcome data was collected at baseline at 4, 6 and 12 months. The primary outcome was the disease specific HRQoL using the Minnesota Living with Heart Failure questionnaire (MLHFQ) at 12 months. Secondary outcomes included death, hospitalisation, generic quality of life (EuroQol-5-Dimension-EQ-5D-5L), psychological well-being (Hospital Anxiety and Depression Scale, HADS), exercise capacity (incremental shuttle walk test-ISWT), and physical activity (accelerometry). Results: We met our recruitment target of 216 patients (mean age 69.8 years, 78.5% male; 80% with New York Heart Association (NYHA) Class II/III). Compared with control, the intervention group was associated with a clinically meaningful improvement in the total MLHFQ score at 12 month follow up of −5.7 (95% CI: −10.6 to −0.7, p=0.025, intention to treat analysis). At 12 months there were a total of 8 deaths – 4 in each group and 19 hospital admissions in the intervention group and 24 in controls – 3 versus 6 HF-related admissions respectively. There was no between group difference in mean EQ-5D-5L (−0.024, –0.091 to 0.04), 0.49), HADS Anxiety score (0.1 (-0.8 to 1.0), 0.83), HADS Depression score (−0.2 (-1.1 to 0.6), 0.56) or in exercise capacity (ISWT in metres: 0.1 (-33.3 to 33.5), 1.0) and physical activity (number of days per week with at least 10 min per day activity >100 millig-unit: 0.2 (-0.4 to 0.7), 0.6). Conclusion: Our findings indicate that the addition of the REACH-HF home-based rehabilitation-intervention to usual care for the management of HFrEF results in clinically important improvements in disease-specific HRQoL and has the potential to reduce hospital admissions. The REACH-HF intervention had no impact on generic HRQoL, psychological well-being, exercise capacity or physical activity.